Prosody in the hands of the speaker - Guellaï, Bahia; Langus, Alan; Nespor, Marina (Frontiers in Psychology, 2014)
In everyday life, speech is accompanied by gestures. In the present study, two experiments tested the possibility that spontaneous gestures accompanying speech carry prosodic information. Experiment 1 showed that gestures provide prosodic information, as adults are able to perceive the congruency between low-pass filtered – thus unintelligible – speech and the gestures of the speaker. Experiment 2 shows that in the case of ambiguous sentences (i.e., sentences with two alternative meanings depending on their prosody) mismatched prosody and gestures lead participants to choose more often the meaning signaled by gestures. Our results demonstrate that the prosody that characterizes speech is not a modality specific phenomenon: it is also perceived in the spontaneous gestures that accompany speech. We draw the conclusion that spontaneous gestures and speech form a single communication system where the suprasegmental aspects of spoken language are mapped to the motor-programs responsible for the production of both speech sounds and hand gestures.